Analisis Perbandingan Risk dan Return antara Saham Konvensional dan Saham Syariah Tahun 2015-2019 - Nina Nicola (JURNAL ILMIAH EDUNOMIKA, 2021)
This study was structured to see and determine the average difference in Risk and Return between conventional stocks in the LQ45 index and Islamic stocks I the Jakarta Islamic Index in 2015-2019. Risk and return is something that investors need to know, especially. This type of research is a descriptive study with a quantitative approach. The sample used in this study amounted to 8 conventional stocks and 8 islamic stocks which were taken from the monthly stock price data during the study period. The Kolmogorov-Smirnov normality test is used to determine whether the different test will use parametric or nonparametric statistics. The results of the analysis show that the risk in islamic stocks is higher than the risk of conventional stocks. As for return, conventional stocks have a higher return when compared to islamic stocks returns. In statistical tests using the Independent t-test with a significance level of 5%, the results obtained for risk and return are not the difference between conventional stocks and islamic stocks. Keyword : Risk; Return; Conventional Stocks; Sharia Stocks